The Effect of Low-Intensity Exercise on Some Post-Exertion Physiological Variables in Developing the Skill of Defending the Court among Volleyball Players - Hamid, Ahmed Walhan; Abdullah, Ali Talal; Farhan, Riad Abdelreda; Abdulridha, Samer Saadoon (Indonesian Journal Publisher, 2025)
To develop low-intensity exercises on some physiological variables after exercise in developing the skill of defending the court among volleyball players. To identify the effect of low-intensity exercises on some physiological variables after exercise in developing the skill of defending the court among volleyball players. The researcher used the experimental method as it is the most appropriate method to address the research problem. The research community was deliberately selected, comprising advanced volleyball players in Diyala Governorate. The research sample was randomly selected by lottery, comprising players from the Hibheb Sports Club and the Muqdadiyah Sports Club. They were divided into two groups: an experimental group and a control group. Hibheb Club represented the experimental group, numbering (14) players, while Al-Wajihiya Club represented the control group (14). (Four) players were selected from both clubs to represent the exploratory experiment. Their results were excluded from the main experiment, resulting in a final sample of (24) players. Low-intensity exercises have shown a clear effectiveness in reducing the concentration of lactic acid in the blood after physical exertion, indicating a significant improvement in the efficiency of the metabolic response and physiological recovery in volleyball players. The training program based on low-intensity exercises contributed to reducing the heart rate in the pre-, during-, and post-effort phases, indicating an improvement in the efficiency of the circulatory-respiratory system and an increase in the body's ability to regulate the heart under the influence of exertion. Forced expiratory volume in the first second (FEV₁) improved significantly after applying the method. The researcher recommends the necessity of integrating low-intensity exercises in a systematic manner into daily training units, especially in the post-effort phases, due to their effect in accelerating recovery and improving the player's physiological indicators. He also recommends employing low-intensity exercises before exertion as part of a dynamic warm-up to improve physiological preparation and activate the circulatory and respiratory systems before entering peak performance.